Transient Receptor Potential Channel 4 Small-Molecule Inhibition Alleviates Migraine-Like Behavior in Mice - Cohen, Cinder Faith; Prudente, Arthur Silveira; Berta, Temugin; Lee, Sang Hoon (Frontiers in Molecular Neuroscience, 2021)
Migraine is a common neurological disorder with few available treatment options. Recently, we have demonstrated the role of transient receptor potential cation channel subfamily C member 4 (TRPC4) in itch and the modulation of the calcitonin gene-related peptide (CGRP), a biomarker and emerging therapeutic target for migraine. In this study, we characterized the role of TRPC4 in pain and evaluated its inhibition as anti-migraine pain therapy in preclinical mouse models. First, we found that TRPC4 is highly expressed in trigeminal ganglia and its activation not only mediates itch but also pain. Second, we demonstrated that the small-molecule inhibitor ML204, a specific TRPC4 antagonist, significantly reduced episodic and chronic migraine-like behaviors in male and female mice after injection of nitroglycerin (NTG), a well-known migraine inducer in rodents and humans. Third, we found a significant decrease in CGRP protein levels in the plasma of both male and female mice treated with ML-204, which largely prevented the development of chronic migraine-like behavior. Using sensory neuron cultures, we confirmed that activation of TRPC4 elicited release of CGRP, which was significantly diminished by ML-204. Collectively, our findings identify TRPC4 in peripheral sensory neurons as a mediator of CGRP release and NTG-evoked migraine. Since a TRPC4 antagonist is already in clinical trials, we expect that this study will rapidly lead to novel and effective clinical treatments for migraineurs.